Microstructural aspects of thermally modified Eucalyptus grandis wood - Djeison Cesar Batista; Juarez Benigno Paes; Graciela Ines Bolzón de Muñiz; Silvana Nisgoski; José Tarcísio da Silva Oliveira (Maderas: Ciencia y Tecnología, 2015)
Thermal modification of wood is a process that has drawn considerable attention of Brazilian researchers, but studies about the effect of this process on wood anatomy are scarce, even in the worldwide literature. The aim of this work was to perform a preliminary analysis of the effect of the Brazilian thermal modification process called VAP HolzSysteme® on the cell dimensions of Eucalyptus grandis wood. The investigated treatments corresponded to three final cycle temperatures (140, 160 and 180 °C), which were compared to untreated wood. Wood anatomy was analyzed qualitatively and quantitatively by scanning electron microscopy (SEM) and optical microscopy, in the latter case to measure the dimensions of fibers, vessel elements and ray parenchyma. The qualitative analysis using SEM indicated that no significant changes occurred on the structure of ray parenchyma, vessels and fibers tissues. Even tyloses was preserved in the vessel elements of thermally modified wood at the highest temperature (180 °C). Likewise, no quantitative changes were observed in the dimensions of fibers, vessels diameter and ray parenchyma height.